Premenstrual syndrome and its association with emotional dysregulation: a comparison between medical and non medical students - Selvarajan, Suganthi; Ajmal, Hiba (International Journal Of Community Medicine And Public Health, 2019)
Background: Premenstrual syndrome is a disorder of menstrual cycle that encompasses varied symptoms ranging from physical, emotional to psychological. Depression and anxiety were considered to be two of the most severely disabling, amongst the varied emotional symptoms, as found by Gotts et al. This study was to find if the stressful life of medicos further dampened their ability to regulate their emotions during PMS. Methods: This was a comparative cross sectional study was carried out between July and October 2018. Female students of first three years studying on Govt. Kilpauk Medical College and JBAS College, Teynamet, were recruited for the study after obtaining written informed consent. Results: The mean PMS score among medicos is 93.791 and the mean PMS score among non-medicos is 88.473. Since the mean score of both the groups is higher than the cut off for PMS as per the PMS Scale, there is occurrence of PMS in both the groups. Further comparing the PMS scores of case and control, the case group consisting of medicos had a higher prevalence compared to the non-medicos. Conclusions: Since there is significant prevalence of PMS among medicos, early diagnosis is crucial. The people with PMS can be given cognitive behavioural therapy. Advising women with PMS to take vitamin B6 can also help in managing this abnormal mood regulatory menstrual disease. Pyridoxine is known to provide great results in the treatment of PMS.